The Historical Construction of School Practices of Agricultural Family Schools in Rio Grande do Sul - Daiane Netto; João Ernesto Pelisari Candido; Marilisa Bialvo Hoffmann; Glauco Schultz (Universidade Federal do Norte do Tocantins, 2024)
In Rio Grande do Sul (RS), since 2010, the Agricultural Family Schools (EFA) have been undergoing an expansion process. There are four schools in this settings at the state, linked to the precepts of Rural Education and the Alternancy Pedagogy. The objective of this work is to describe the historical trajectory of Rural Education, the Alternancy Pedagogy and the relevant legislation in RS. Furthermore, it intends to evaluate its influence in the process of expansion and organization of EFA. The research was carried out in two stages: the exploratory study and the field research. Data collection was carried out through semi-structured interviews with the EFA's pedagogical coordinators and monitors. The results demonstrate that successful experiences with the Alternancy Pedagogy are directly related to the participation of the community and rural social movements. It was possible to understand that in RS the specific legislation also benefited the process of increasing the number of EFA through joint actions with the State Committee for Rural Education.